Food as a source of exposure to nickel - Monika Mania; Małgorzata Rebeniak; Jacek Postupolski (National Institute of Public Health - National Institute of Hygiene, 2019)
According to the European Food Safety Authority (EFSA), food is the main source of nickel intake by the general population. Based on the risk assessment, EFSA determined the tolerable daily intake of this element (TDI) from all sources at the level of 2.8 μg/kg body weight, which is for an adult 196 μg, while for a child 56 μg. The Benchmark Dose Lower Confidence Limit (BMDL10) associated with dermatitis at 1.1 μg/kg body weight was also determined as well as the Margin of Exposure (MOE). Nickel intake in the Member States varies and depends on consumption habits. CONTAM Panel of EFSA considered the unlikely possibility of developing cancers related to the intake of nickel with food. According to experts, other harmful effects on the human body are more often identified. An additional aspect requiring further investigations that will allow an actual estimation of exposure associated with intake of this element by various groups of population is the issue of nickel absorption in the human body. The review of the EFSA opinion on the request of the European Commission planned in the near future based on the collected data as part of the action of the Commission Recommendation (EU) 2016/1111 on monitoring the presence of nickel in food will contribute to taking appropriate actions related to consumer protection, including the most vulnerable groups of population.